Foucault Before the Collège de France. (January 2023) - Elden, Stuart; Irrera, Orazio; Lorenzini, Daniele
This introduction to the special issue 'Foucault Before the Collège de France' surveys Foucault's work in the first part of his career. While there is a familiar chronology to the books he published in the 1960s – from History of Madness to The Archaeology of Knowledge – the story can be developed in relation to his articles, his translations, his early publications and manuscripts, and his teaching. Looking at the programme of posthumous publication of many of his courses and unfinished manuscripts, this introduction discusses key themes, and introduces the papers of the special issue which analyse these texts in detail. It concludes with some general thoughts about what these hitherto neglected or hidden sources tell us about the work of Foucault. Although it adds some cautions about their use, we believe the texts and lectures analysed in this issue and others from the period before the Collège de France add valuable insights into our understanding of Foucault's intellectual development, his interests and plans, and his enduring influence on a variety of fields in the humanities and social sciences.